Local and Global Visual Processing in 3-Year-Olds With and Without Autism - Nilsson Jobs, E.; Falck-Ytter, T.; Bolte, Sven (Springer New York LLC, 2018)
© 2018 The Author(s) Research on visual local and global perception in Autism Spectrum Disorder (ASD) is incomplete in young children. We investigated 35 three-year-old siblings of children with ASD, either diagnosed (n = 12) or not diagnosed (n = 23) with ASD as well as 14 controls with typical development and with no family history of ASD. Data from the local tasks Children’s Embedded Figures Test, Hidden Pictures, Figure-Ground and the global tasks Closure and Fragmented Picture Test were collected. Enhanced performance on the local task Hidden Pictures differentiated children with ASD from the other groups. Implications of these results are discussed.